ANALISIS IMPLEMENTASI DIGITAL PUBLIC RELATIONS PADA KONTEN INSTAGRAM @ALAMINUNIVERSAL - Syafaat, Muhammad; Wahyudin, Delmia (Universitas Prof. Dr. Moestopo (Beragama), 2020)
Hajj and Umrah are one of the five obligations for Muslims throughout the world. Data from the Association of Muslim Pilgrimage and Umrah Pilgrims of the Republic of Indonesia (AMPHURI) states that the total Muslim population in Indonesia reaches 215,000,000 inhabitants or equal to 87% of Indonesia's population and 24% of the total Muslim population in the world. Al Amin Universal as one of the pioneers in organizing Hajj and Umrah in Indonesia has a strategy in attracting markets and maintaining its reputation. By utilizing Digital Public Relations as an instrument to attract the market through Instagram @alaminuniversal social media accounts. The aim of this researcher is to find out the extent of the implementation of the strategies that have been carried out by companies in maintaining and building a company's reputation through the digital content that is displayed. The method used in this study is interpretative qualitative and centralized interview data collection techniques. The main theory used in this research is Online Public Relations (Philip & Young). The results of this study indicate that the Digital Public Relations Implementation on Instagram @alaminuniversial accounts has been very scalable in accordance with the theory used, evidenced by the strong elements of Transparency and Richness in Content and Reach in each of their posts.